AN IN-DEPTH PHARMACOGNOSTICAL VIEW OF SUNISHANNAKA (MARSILEA QUADRIFOLIA LINN) – A VALUABLE PTERIDOPHYTE - Jilu Joy,; Sara Monsy Oommen,; P.Y Ansary, (International Journal of Ayurveda and Pharma Research, 2019)
Sunishannaka (Marsilea quadrifolia Linn) is a known pteridophytic creeping aquatic fern, commonly known as European Water Clover belonging to the family Marsileaceae which is being used extensively since Samhita period. According to Acharya Vagbhata, it is included among Pathyaahara or Nityasevaniyaahara which itself shows its nutritional importance. Pteridophytes have considerable importance in traditional pharmacopoeias, whereas scientific studies on pharmacognosy of this group are scanty. Records of indigenous medicinal knowledge about pteridophytes need to be given top priority to aid the protection of such knowledge before they vanish from present day traditional healers. This work aims at understanding the organoleptic features and microscopic details of leaf, petiole and rhizome (stem) and root of Marsilea quadrifolia Linn. Even though the drug Sunishannaka (Marsilea quadrifolia Linn) is being used by traditional Vaidyas, but the detailed study regarding the microscopical aspects of the plant has not been documented in detail. So the present paper will definitely throw a light towards the microscopical characters of the plant which is much essential to provide a key towards identification of the plant source and to prevent any adulterations.